Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.heliyon.2017.e00304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NiO/SiO2 on thermo-chemical conversion of waste cooking oil to hydrocarbons

Abstract: Increase in organic waste generation, dwindling nature of global oil reserves coupled with environmental challenges caused by waste oil disposal and burning of fossil fuels necessitated the need for alternative energy resources. Waste cooking oil obtained from the frying fish outlet was analyzed for its physicochemical properties using ASTM D-975 methods. Acid and Iodine values of the oil were 30.43 ± 0.32 mgKOH/g and 57.08 ± 0.43 mgI2/100 g respectively. Thermo-chemical conversion of the oil using NiO/SiO2 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Knowledge that is known about the usual conventional fuels is nothing to write good about as they are known for polluting air by emissions of sulfur dioxides, carbon-dioxides, particulate matter and other gases which are detrimental to the environment as it contributes to global warming problems [1] Even with this, we are still charged with the responsibility of harnessing energy from other green sources because "Energy sources are the main driver of economic growth and social development of a country [2] and if we want to progress as a country, it is of paramount important that we should search for a greener alternative source of energy. Naveen [3], also noted that there is an exponential increase in the consumption of fossil fuel both in developed and developing nations; and it is estimated that these fuels shall be exhausted by the turn of 22 nd century.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge that is known about the usual conventional fuels is nothing to write good about as they are known for polluting air by emissions of sulfur dioxides, carbon-dioxides, particulate matter and other gases which are detrimental to the environment as it contributes to global warming problems [1] Even with this, we are still charged with the responsibility of harnessing energy from other green sources because "Energy sources are the main driver of economic growth and social development of a country [2] and if we want to progress as a country, it is of paramount important that we should search for a greener alternative source of energy. Naveen [3], also noted that there is an exponential increase in the consumption of fossil fuel both in developed and developing nations; and it is estimated that these fuels shall be exhausted by the turn of 22 nd century.…”
Section: Introductionmentioning
confidence: 99%
“…The high free fatty acids content in the palm oil sludge (25.25%) can result into soap formation in the presence of potassium hydroxide during transesterification reaction of the oil. Studies also shown that high FFA reduces catalyst effectiveness and decreases the production yield [27,29]. Hayyan et al [28] & Usam et al [30] reported the free fatty acid value of palm oil sludge to be 74.8% and 22.3%.…”
Section: Characterization Of Palm Oil Sludge Used In Biodiesel Producmentioning
confidence: 99%
“… 8 The efficiency of heterogeneous catalysts is a function of surface area, chemical stability, surface reactivity, recovering method, and the concentration of catalytic sites. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%